The effect of cooling on machining and phase transformation responses of Ni-rich NiTiHf high-temperature shape memory alloy - KAYNAK, YUSUF (My University, 2022)
© 2022A Ni-rich Ni50.3Ti29.7Hf20 (at. %) high-temperature shape memory alloy was machined under different cooling conditions, specifically cryogenic cooling and flood cooling, and results were compared with those from dry machining. The effects of cooling on machinability measures such as tool wear, cutting forces and surface quality were evaluated for various cutting speeds. Microhardness, phase transformation temperatures and latent heat of transformation corresponding to the machined specimens were determined using hardness and differential scanning calorimetry tests. Cryogenic cooling was found to notably improve the machinability of the Ni-rich NiTiHf alloy by reducing tool wear, cutting force and surface roughness. This study provides clear indication that the machining process alters the phase transformation temperature of the Ni-rich NiTiHf alloy. After the machining process, austenite finish temperature of specimens increased by 5–10% depending on the machining conditions. The smallest amount of latent heat required for transformation (ΔH) was obtained for each of the two specimens: 2.33 J/g (exothermic) for the cryogenically machined specimen and 3.38 J/g (exothermic) for the specimen machined under flood cooling.
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; MÜHENDİSLİK, İMALAT; Mühendislik; Mühendislik, Bilişim ve Teknoloji (ENG); ENGINEERING, MANUFACTURING; ENGINEERING; Engineering, Computing & Technology (ENG); Industrial and Manufacturing Engineering; General Engineering; Safety, Risk, Reliability and Quality; Engineering (miscellaneous); Physical Sciences; High-temperature shape memory alloy; Cryogenic machining; Machining performance; Phase transformation; NiTiHf; TOOL-WEAR; BEHAVIOR; DRY; CARBIDE